Conflict resolution and religious behavior: Achieving authentic happiness among married individual - Dea Intan Purwanti; Annisa Fitriani; Rahmad Purnama (Proyeksi, 2026)
This study aims to examine the relationship between conflict resolution, religious behavior, and authentic happiness among married couples in Lampung Province. This research employed a quantitative approach. The sample consisted of 100 married individuals residing in Lampung Province, selected through purposive sampling based on the following criteria: having been married for at least five years, having experienced marital conflict, not currently undergoing divorce or legal proceedings, and regularly engaging in religious practices. Data were collected through self-report questionnaires using a Likert scale. The data were analyzed using multiple linear regression analysis. The results indicated that the independent variables jointly had a significant effect on authentic happiness (F = 82.797, p < 0.05). Conflict resolution and religious behavior together explained 62.3% of the variance in authentic happiness, while the remaining 37.7% was accounted for by other variables not examined in this study.